The role of perinatal palliative care following prenatal diagnosis of major, incurable fetal anomalies: a multicentre prospective cohort study. (8th November 2021) - de Barbeyrac, C; Roth, P; Noël, C; Anselem, O; Gaudin, A; Roumegoux, C; Azcona, B; Castel, C; Noret, M; Letamendia, E; Stirnemann, J; Ville, Y; et al.
Abstract : Objective: To describe prenatal decision‐making processes and birth plans in pregnancies amenable to planning perinatal palliative care. Design: Multicentre prospective observational study. Setting: Nine Multidisciplinary Centres for Prenatal Diagnosis of the Paris‐Ile‐de‐France region. Population: All cases of major and incurable fetal anomaly eligible for TOP where limitation of life‐sustaining treatments for the neonate was discussed in the prenatal period between 2015 and 2016. Methods: Cases of congenital defects amenable to perinatal palliative care were prospectively included in each centre. Prenatal diagnosis, decision‐making process, type of birth plan, birth characteristics, pregnancy and neonatal outcome were collected prospectively and anonymously. Main outcome measure: Final decision reached following discussions in the antenatal period. Results: We identified 736 continuing pregnancies with a diagnosis of a severe fetal condition eligible for TOP. Perinatal palliative care was considered in 102/736 (13.9%) pregnancies (106 infants); discussions were multidisciplinary in 99/106 (93.4%) cases. Prenatal birth plans involved life‐sustaining treatment limitation and comfort care in 73/736 (9.9%) of the pregnancies. The main reason for planning palliative care at birth was short‐term inevitable death in 39 cases (53.4%). In all, 76/106 (71.7%) infants were born alive, and 18/106 (17%) infants were alive at last follow‐up, including four with a perinatal palliative care birth plan. Conclusions: Only a small proportion of severe and incurable fetal disorders were potentially amenable to limitation of life‐sustaining interventions. Perinatal palliative care may not be considered a universal alternative to termination of pregnancy. Tweetable abstract: Perinatal palliative care is planned in 10% of continuing pregnancies with a major and incurable fetal condition eligible for TOP. Tweetable abstract: Perinatal palliative care is planned in 10% of continuing pregnancies with a major and incurable fetal condition eligible for TOP.